Synthesis of rGO/ZnO complex and its effects on the thermal behaviour of PLA - Goh, Min Hao. (2013)
To have an effect on the combustion properties of polylactic acid (PLA), reduced graphene oxide/zinc oxide (rGO/ZnO) complex was synthesized and incorporated into the former. The fundamental concept behind this approach is to benefit from the fire retardancy properties of both ZnO and layered rGO. That is, Zn-based compounds were reported to be effective catalysts for dehydrogenation (and subsequent carbonization) in some polymer systems; while layered nanoparticles were proven to greatly reduce heat and mass loss rates during combustion of a polymer nanocomposite. But combustion tests were out of scope of the present work, which is limited to synthesis and preliminary characterization of the nanofillers and composites. From the results, it was noticed that the ZnO acted as a catalyst that degraded the molecular weights of PLA matrix via transesterification reactions even during processing. This degradation significantly influenced the thermal stability of the materials.